Disaster Risk Perception and Communication in Flood-prone Areas in Albania: A Comparison of Urban and Rural Settings - Pojani, Elona; Hudhra, Xhoana; Pojani, Dorina; Hassel, Henrik (Geographica Pannonica, 2025)
This study examines disaster risk perception and communication in Albania, focusing on two districts in the cities of Tirana and Fier and the villages of Novosela and Dajç, all affected by severe flooding in recent years. The research highlights how dimensions of national culture - particularly fatalism and attachment to home and hearth - interact with contextual, psychological, and demographic characteristics to shape flood risk perceptions. Quantitative analysis using surveys (N=104) and ORL regression models shows that disaster risk tolerance is influenced by location, household income, and prior exposure to natural disasters. Urban residents are less tolerant of risk, while higher-income individuals and those with previous disaster experience show greater tolerance. Qualitative interviews reveal that city dwellers often perceive floods as inevitable, while rural participants emphasize communal coping and local knowledge.
Keywords: disaster risk perception; disaster risk communication; floods; Albania; rural areas; urban areas